Hijrah dalam Narasi Etika Sufistik - Lina Munadlirotul Qomariyah, Lina; Fathul Harits, Harits (Mahad Aly Al Fithrah, 2021)
Hijrah which interpreted to move, now become a new role model in society. Hijrah often interpreted as the process of moving from behavior haven’t accordance with sharia to behavior as accordance with sharia. This is shown by lifestyle, especially in terms of dress. Now hijrah glow not more than a symbol, but poor ethics. Whereas the meaning of hijrah is not as narrow as today, because basically, hijrah always talked about inner displacement in this era, has a different term with Prophet Muhammad’s era who was more dominant in moving physically. But that doesn't change the meaning of Hijrah itself. This research uses descriptive qualitative research methods. Here, tasawuf comes as a continuous scientific integrity. Sufi teachings as the roots of moderate Islam. Through ethics according perspective sufi, hijrah that undergoes a shift meaning can be actualized through uzlah, muraqobah, musabahah, raja'. Thus, the meaning of hijrah today can be moved, both physically and mentally, so that hijrah is not just a symbolization